Features of Logistic System Adaptive Management - Natalya Voznenko; Teodora Roman (CES Working Papers, 2015)
The study presents literature survey on enterprise logistic system adaptive management place and structure in the general enterprise management system. The theoretical basics of logistic system functioning, levels of its management and its effectiveness had been investigated. The role of adaptive management and its types had been scrutinized. The necessity of creating company's adaptive regulator such as its economic mechanism had been proved.
Keywords: L29; 330; logistic system; levels of enterprise management; enterprise adaptive management; active adaptation; passive adaptation